Basic Psychological Needs Satisfaction and Frustration, Stress, and Sports Injury Among University Athletes: A Four-Wave Prospective Survey - Li, Chunxiao; Ivarsson, Andreas; Lam, Lawrence T.; Sun, Jian (Frontiers in Psychology, 2019)
The prevalence of sports injury among athletes is rather high, suggesting the need to better understand the causes of sports injury, including the risk factors, for preventive purposes. Grounded in Basic Psychological Needs Theory (BPNT) and the Model of Stress and Athletic Injury, the aim of this four-wave prospective survey study was to investigate the relationships among basic psychological needs satisfaction and frustration, stress responses, and sports injury. Study variables, including basic psychological need satisfaction/frustration, and perceived stress, were measured using a survey from 112 university athletes at the 1st, 2nd, and 3rd months of the study. Sports injury was assessed using a self-report form at the 2nd, 3rd, and 4th months of study. Results of the Bayesian multilevel analysis showed that basic psychological need satisfaction negatively predicted sports injuries, whereas stress was a positive predictor. In addition, basic psychological need satisfaction had an indirect effect on injury occurrence via stress. However, basic psychological need frustration did not predict sports injury. BPNT is a viable model to provide additional explanations to psychological risk factors of injury. Intervention programs may be formulated based on the evidence obtained on the model.